Pengaruh Personalitas (Dark Triad), Religiusitas-Spiritualitas Terhadap Niat Kewirausahaan Pada Remaja Di DKI Jakarta - Fakhruddin Mart; Rizki Mulyadi; Indira Zahra (Universitas Persada Indonesia YAI, 2020)
The participation of young people in the Creative Economy Sector is needed. Amid the effects of thepandemic, which is the effect of the global economic downturn, the results of a recent survey on May 14-202020 of American teenagers showed that teenagers remain open to becoming entrepreneurs and startingbusinesses. The question is about how the intention to become entrepreneurial in Indonesian youth,especially in DKI Jakarta. In this case, we focus on research on how the influence of personality, religiosity,and spirituality as well as entrepreneurial self-efficacy affects entrepreneurial intentions. Data from asample of 215 adolescents from schools in Central Jakarta and West Jakarta were then processed using theStructure Equation Model (SEM) technique through the use of SmartPLS3 software. The results show thatMachiavellianism does not have a significant effect, in contrast to narcissism which has a positive effect,and psychopathy which has a greater negative effect on entrepreneurial intentions than the positiveinfluence of religious activity and faith-based coping on entrepreneurial intentions. This study concludedthat psychopathic personality has a direct negative effect on entrepreneurial intention. Meanwhile,narcissism, religious activities, and faith-based coping have a positive effect on entrepreneurial intentions,but entrepreneurial self-efficacy is needed as a mediator for religious activities to have a better effect on theentrepreneurial intention of adolescents in DKI Jakarta